The recovery effect of Vitamin C on structural alterations due to Streptozotocin-Induced diabetes in rat testicular tissues - Baloglu, Fatma Kucuk; Tas, Damla Guldag; Yilmaz, Okkes; Severcan, Feride (Pergamon-Elsevier Science Ltd, 2023)
Type I Diabetes is a multisystem disease that causes alterations in carbohydrate, protein, and fat metabolisms due to hyperglycemia. It has an extensive pathology, especially the mechanism involving oxidative stress is still complex. Type I diabetes is correlated with increased formation of free radicals and decreased levels of anti-oxidant potential. Vitamin C (Vit C) is a powerful antioxidant that participates in antioxidant defense, protecting lipid membranes and proteins from oxidative damage by donating electrons to free radicals.The effect of type I diabetes and the recovery role of Vit C on the structure and composition of the biomol-ecular content of testicular tissue is still unknown. Therefore, the current study aimed to investigate the alter-ations in the biomolecules of rat testes due to Streptozotocin (STZ)-induced type I diabetes using Attenuated Total Reflectance (ATR)-Fourier Transform Infrared (FTIR) spectroscopy and histological staining. The results revealed that the biomolecular structure and composition of testicular tissue are highly affected due to the development of diabetes. We obtained decreased saturation levels and increased unsaturation index in the lipids indicating the presence of lipid peroxidation in the diabetic state. The elevated lipid peroxidation levels have been implicated in the pathogenesis of naturally occurring and chemically induced diabetes. On the other hand, the protein content of diabetic rat testicular tissue was shown to decrease considerably, indicating an increase in proteolysis processes. Supporting the ratio of protein structural and conformational change, protein secondary structural components were also found to alter substantially in the diabetic state. Diabetes was also shown to lead to a decrease in the content of nucleic acids compared to proteins. These diabetes-induced alterations were found to be substantially recovered with the administration of Vit C. Although different doses and administration types of Vit C have been reported in the literature, there is no consensus yet. Therefore, we used three different doses of Vit C in our study as high (100 mg/kg/day), medium (50 mg/kg/day) and low (15 mg/kg/day) doses intra-peritoneally in the present study, and the medium dose was found to be the most effective in the recovery from the diabetes-induced structural damages on rat testicular tissue. Vit C may have a therapeutic effect to be used as a complementary therapy in the treatment of diabetes.
Keywords: Type I diabetes; Vitamin C; Testicular tissue; ATR-FTIR spectroscopy; Biomolecular Structure; Protein Secondary Structure